Changing Shapes of Glycogen–Autophagy Nexus in Neurons: Perspective from a Rare Epilepsy - Singh, Pankaj Kumar; Singh, Sweta (Frontiers in Neurology, 2015)
In brain, glycogen metabolism is predominantly restricted to astrocytes but it also indirectly supports neuronal functions. Increased accumulation of glycogen in neurons is mysteriously pathogenic triggering neurodegeneration as seen in ‘Lafora disease’ and in other transgenic animal models of neuronal glycogen accumulation. Lafora disease is a fatal neurodegenerative disorder with excessive glycogen inclusions in neurons. Autophagy, a pathway for bulk degradation of obsolete cellular constituents also degrades metabolites like lipid and glycogen. Recently, defects in this pathway emerged as a plausible reason for glycogen accumulation in neurons in Lafora disease, although some contradictions prevail. Albeit surprising, a reciprocal regulation of autophagy by glycogen in neurons has also just been proposed. Notably, increasing evidences of interaction between proteins of autophagy and glycogen metabolism from diverse model systems indicate a conserved, dynamic and regulatory cross-talk between these two pathways. Concerning these findings, we herein provide certain models for the molecular basis of this cross-talk and discuss its potential implication in the pathophysiology of Lafora disease.